Cover Feature: Cation‐/Anion‐Based Physicochemical Mechanisms for Anodically Coloring Electrochromic Nickel Oxide Thin Films (ChemElectroChem 7/2022). Issue 7 (3rd March 2022) - Qu, Hui‐Ying; Wang, Xiyang; Chen, Ding; Bai, Zhihao; Wang, Nannan; Zhu, Yan‐Qiu; Tong, Zhangfa; Ji, Hongbing; Niklasson, Gunnar A.
Abstract : The Cover Feature shows Cl − and Li + ions adsorb onto the surface of nickel oxide and are accumulated upon extended electrochromic cycling in an electrolyte of 1 M LiClO4 ‐PC. Adsorption of Cl − takes place at high potentials and leads to darkening of NiO, while bleaching at lower potentials happens via the desorption of Cl − and/or adsorption of Li + . DFT calculations provide further insights for the band structures and how they change when Li + and Cl − are adsorbed. More information can be found in the Research Article by H.‐Y. Qu et al .